2020
DOI: 10.1177/0959354320973752
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances in dialogue and metacognition: A renewed way to understand and respond to alterations in self-experience in psychosis

Abstract: A dialogical model of psychosis proposed that the collapse of dialogue may explain the alterations in sense of self and agency observed in psychosis. This view was hampered by lack of clarity regarding the processes that support or hinder dialogue. Since then, research on metacognition has offered an alternative but also partially complementary approach. To explore this issue a brief history of the original dialogical conceptualization of psychosis and the difficulties that it confronts is offered along with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 67 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…With the deficits in self-reflectivity and decentration found in psychosis, persons would be unlikely to have a working sense of themselves as having multiple facets which may be contradictory and change over time. Without this quality of partiality, the cohesion of a larger sense of self would be threatened by inconsistencies and dissolve [ 137 , 138 ]. This could result in a sense of self in which different aspects of the self are experienced as active but unrelated to one another, where no aspect of the self is distinguished from another, and hence all are experienced as absent.…”
Section: The Unique Experimental Theoretical and Clinical Implications Of Metacognitive Research In Psychosismentioning
confidence: 99%
“…With the deficits in self-reflectivity and decentration found in psychosis, persons would be unlikely to have a working sense of themselves as having multiple facets which may be contradictory and change over time. Without this quality of partiality, the cohesion of a larger sense of self would be threatened by inconsistencies and dissolve [ 137 , 138 ]. This could result in a sense of self in which different aspects of the self are experienced as active but unrelated to one another, where no aspect of the self is distinguished from another, and hence all are experienced as absent.…”
Section: The Unique Experimental Theoretical and Clinical Implications Of Metacognitive Research In Psychosismentioning
confidence: 99%
“…Across psychological disciplines, the concept of metacognition has been used to refer to persons' awareness of their thoughts and feelings and how they adjust their thoughts and actions as a result (Flavell, 1979 ; Semerari et al, 2003 ; Moritz and Lysaker, 2018 ). In research on disturbances in subjectivity in psychosis, metacognition has been used to operationalize the processes that enable a reflexive awareness of oneself and others (Lysaker and Lysaker, 2020 ; Lysaker et al, 2020b ). Specifically, this work has used an integrative model of metacognition that considers metacognition as the spectrum of activities that allow persons to become aware of specific cognitive, emotional and bodily experiences and to integrate these into a broader and evolving sense of their and others' unique identities and places in the world (Lysaker and Hasson-Ohayon, 2021 ).…”
Section: Metacognition and Disturbances In Social Functioningmentioning
confidence: 99%
“…Key for the study of social function in psychosis are at least two features of this model. The first is that metacognition is always an intersubjective activity (Hasson-Ohayon et al, 2020 ), such that any sense formed about oneself or others is always done so with an actual or potential partner who can share that sense (Lysaker and Lysaker, 2020 ). Second, in this model sense of self and sense of others, while naturally related, can be measured separately.…”
Section: Metacognition and Disturbances In Social Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Persons know themselves only as they experience themselves experiencing the world. It has been suggested that these kinds of subjective alterations may be more effectively understood if one considers how they lead to a loss of a sense of purpose, meaning and possibility in life, and returning to the issue of intersubjectivity, how they also lead to a loss of one's sense of place and position relative to others and one's community (Lysaker & Lysaker, 2020; Lysaker et al, 2020).…”
mentioning
confidence: 99%